2017
DOI: 10.1128/jb.00281-17
|View full text |Cite
|
Sign up to set email alerts
|

TetR Family Transcriptional Regulator PccD Negatively Controls Propionyl Coenzyme A Assimilation in Saccharopolyspora erythraea

Abstract: Propanol stimulates erythromycin biosynthesis by increasing the supply of propionyl coenzyme A (propionyl-CoA), a starter unit of erythromycin production in Propionyl-CoA is assimilated via propionyl-CoA carboxylase to methylmalonyl-CoA, an extender unit of erythromycin. We found that the addition of-propanol or propionate caused a 4- to 16-fold increase in the transcriptional levels of the SACE_3398-3400 locus encoding propionyl-CoA carboxylase, a key enzyme in propionate metabolism. The regulator PccD was pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…It is worthwhile to note that genetic engineering of TFR elements has been shown to increase the yields of valuable antibiotics in industrial settings (13)(14)(15). Nonetheless, distinct from research related to TFRs for the biosynthesis of avermectin and erythromycin (13,(15)(16)(17)(18)(19), insights into the regulatory role of TFRs in lincomycin biosynthesis have not been reported. In the genome of S. lincolnensis LCGL, a derivative of S. lincolnensis LC-G with artificial synthetic 4ϫattB ⌽C31 (20), we identified 123 putative TFRs based on BLAST analysis with Pfam PF00440 (TetR_N) and the genome annotation of S. lincolnensis LC-G.…”
mentioning
confidence: 99%
“…It is worthwhile to note that genetic engineering of TFR elements has been shown to increase the yields of valuable antibiotics in industrial settings (13)(14)(15). Nonetheless, distinct from research related to TFRs for the biosynthesis of avermectin and erythromycin (13,(15)(16)(17)(18)(19), insights into the regulatory role of TFRs in lincomycin biosynthesis have not been reported. In the genome of S. lincolnensis LCGL, a derivative of S. lincolnensis LC-G with artificial synthetic 4ϫattB ⌽C31 (20), we identified 123 putative TFRs based on BLAST analysis with Pfam PF00440 (TetR_N) and the genome annotation of S. lincolnensis LC-G.…”
mentioning
confidence: 99%
“…For an insertional deletion of the pccD gene in S. erythraea E3, a previously described homologous recombination strategy was used (29). Briefly, 1.5-kb DNA fragments upstream and downstream of the pccD gene locus were amplified from S. erythraea E3 genomic DNA by PCR using the primer pairs pUC3396upF/R and pUC3396dwF/R ( Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…In this study, ΔgdhA1 and ΔBcdhE1 mutants demonstrated that the bkd operon plays an important role in BCAA degradation in S. erythraea. PccD was also demonstrated to negatively control the propionyl-CoA carboxylase genes (pccBCA) in S. erythraea (29). The pccBC and pccA operons were shown to have a major function in propionyl-CoA assimilation.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…One part was used to detect the dry cell weight (DCW) according to the previous method [40], and the other was used to analyze intracellular propionyl-CoA. Intracellular propionyl-CoA levels were detected using a modified method previously described by Xu et al [41]. Cells cultures were harvested and quenched in liquid nitrogen and washed twice with precooled phosphate-buffered saline (PBS, pH 8.0), then added with lysis buffer (10% trichloroacetic acid and 2 mM dithiothreitol), and repeatedly frozen and thawed four times using liquid nitrogen ice water, then sonicated on ice for 5 min (work 5 s, stop 5 s) using an ultrasonic disintegrator (JY96-IIN; Ningbo Xinzhi Instruments Inc., Ningbo, China).…”
Section: Determination Of Intracellular Propionyl-coa Concentrationsmentioning
confidence: 99%